Isolation of differentially regulated genes in lung cancer cell line by arbitrarily-primed reverse transcription polymerase chain reaction / Nur Hidayah Ismail - Ismail, Nur Hidayah (2013)
Lung cancer is among the five main types of cancer leading to overall cancer mortality contributing about 1.3 million deaths per year globally (Khurana, 2005). The factor that lead to the lung cancer to human is primarily due to bad habit of smoking which when there is a restriction of tobacco smoking can lower the possibility of lung cancer. The aim of the study is to examine the antioxidant and anti-proliferative effects of Gelam honey in lung cancer cell line A549 and also to determine any difference in gene expression of lung cancer that being treated with Gelam honey with the untreated lung cancer. Gelam honey becomes preference because antioxidant activity is significantly higher than the other honey due to its higher phenolic content. The antibacterial system of honey able to get rid the reactive hydroxyl radicals which under the control of antioxidant action of honey (Aljadi & Kamaruddin, 2004). Gene fishing kit was used to generate gene expression profiles between gelam honey treated A549 cells versus untreated cells. Unique bands were cloned using TOPO TA Cloning Kit and sequenced.